Repetitive sequences in complete and defective genomes of Herpesvirus saimiri. - Fleckenstein, B (1975)
Two types of Herpesvirus saimiri genomes can be isolated from purified virions: (i) the M genome is a double-stranded, liniear DNA molecule with a mean contour length corresponding to 89 times 10-6 daltons. The M genome contains about 70% of unique sequences (light DNA, 36% guanine plus cytosine) and 30% reiterated sequences (heavy DNA, 71% guanine plus cytosine). (ii) the H genome is composed of heavy DNA only and is more heterogeneous in size. The sequences in the H genome are up to 40-fold reiterated, indicating defectiveness of this type of genome. The repetitions in the H genome and the M genome cross-hybridize almost completely and have identical kinetic complexity (2.8 times 10-6 daltons). DNA infectivity studies by using the calcium phosphate and the DEAE-dextran method gave further evidence that H genomes are defective: no infectious virus was recovered from permissive cells treated with heavy DNA, whereas M genome-infected cells developed cytopathic changes after 11 to 56 days. Defective H genomes were present in the progeny virus two passages after transfection.